Estratégias para o desenvolvimento de célula eletroquímica em papel visando à determinação de fosfato - Nascimento, Hadassa Vaz [UNIFESP] (2021)
Phosphorus is a chemical element of fundamental importance for life on Earth, as it is part of the biological cycles of several living beings. The excess of phosphate compounds in aquatic environments caused by human actions, cause eutrophication of rivers and lakes. In this context, this work studied the electrochemical behavior of the phosphate using the cyclic voltammetry technique and used an electrochemical cell on paper to identify phosphate. The strategy employed used graphite mines to build the working electrode and the auxiliary electrode. For this, a study carried out from a selection of graphites showed that H graphite is the best option for a working electrode, because its balanced composition of carbon and clay allows the current peaks to be formed with an excellent definition and without adsorption of material. After modifying this electrode with a dispersion of Vulcan® XC 72, there was an increase in signal amplitude, which was lost after successive analysis tests with the same modifier layer. The reference electrode, also built in this work and used in conventional analyzes, made with calomel or silver, was removed from the system and the potential shifted to a more negative region as expected, but the voltammetric profile remained stable, despite the small loss in current amplitude, with tests with hexacyanoferrate (III). This loss of amplitude did not occur for phosphomolybdenum. For the development of the cell on paper, strategies based on the stamping process, construction with modeling of the wax, cutouts of sulfite paper and filter paper and the technique of printing with wax based on microfluidic devices on paper (µPADs) were tested, the last being the one that presented reliable results to make the paper electrochemical cell selective to the phosphate ion.